Antibodies to a trypsin sensitive pancreatic antigen in chronic inflammatory bowel disease: specific markers for a subgroup of patients with Crohn's disease. - Seibold, F (1991)
The presence of antibodies against pancreatic juice (PAB) in patients with Crohn's disease has recently been reported. In our study sera from 273 patients with inflammatory bowel disease (222 with Crohn's disease, 51 with ulcerative colitis) have been examined for PAB and also for antibodies against gut tissues by means of indirect immunofluorescence. PAB were found in 68 of the 222 patients with Crohn's disease (31%), with titres ranging from 1/10 to 1/1280, and in only two patients with ulcerative colitis (4%), with titres of 1/20. None were found in 198 patients with various chronic inflammatory diseases and healthy control subjects. No differences were found between the PAB positive and negative patients when the following parameters were compared: disease activity (Crohn's disease activity index), involvement of bowel segments, incidence of extraintestinal disease, or treatment with anti-inflammatory drugs. Only seven of the patients with Crohn's disease had a history of pancreatic disease and of these, four had detectable pancreatic antibodies. Longitudinal observations of 40 patients with Crohn's disease showed a stable pattern for PAB, independent of disease activity and treatment. Partial characterisation of the PAB antigen, isolated from pancreatic juice, showed a trypsin sensitive macromolecular protein of more than 10(6) daltons not identical with a panel of defined exocrine pancreatic proteins. By contrast, antibodies against goblet cells (GAB) were found in 13 of 51 patients with ulcerative colitis (29%) and in none of the patients with Crohn's disease or control subjects. PAB were found as a highly specific serological marker for Crohn's disease and GAB for ulcerative colitis, but the relevance of PAB and GAB in the pathogenesis in Crohn's disease remains unclear.